Measurement of Interfacial Profiles of Wavy Film Flow on Inclined Wall - Nurrina, Rosli; K., Amagai (IOP Publishing, 2016)
Falling liquid films on inclined wall present in many industrial processes such as in food processing, seawater desalination and electronic devices manufacturing industries. In order to ensure an optimal efficiency of the operation in these industries, a fundamental study on the interfacial flow profiles of the liquid film is of great importance. However, it is generally difficult to experimentally predict the interfacial profiles of liquid film flow on inclined wall due to the instable wavy flow that usually formed on the liquid film surface. In this paper, the liquid film surface velocity was measured by using a non-intrusive technique called as photochromic dye marking method. This technique utilizes the color change of liquid containing the photochromic dye when exposed to the UV light source. The movement of liquid film surface marked by the UV light was analyzed together with the wave passing over the liquid. As a result, the liquid film surface was found to slightly shrink its gradual movement when approached by the wave before gradually move again after the intersection with the wave.